CHARACTERIZATION AND STATIC RESERVOIR MODELLING LECS A AND B INTERVAL, NGIMBANG FORMATION, NORAH FIELD, NORTH EAST JAVA BASIN - Vasius Rosen, Boni
Norah Field is one of the gas producing fields in the Kangean Block, North East Java Basin. The field has an area about 70 km2 and has started production since 1994. The study was conducted at the LECS A & LECS B reservoir intervals which are part of the Ngimbang Formation using data from eight wells in the study area. The study was conducted to determine facies & depositional environments, petrophysical properties and estimates of original gas in place (OGIP). Datas used in this study are rock description report (core, side wall core , and cutting), biostratigraphy report, log data, and well test data. The research interval is Late Eocene Clastic Sandstone (LECS) which is a clastic part of the Ngimbang Formation with the age of Late Eocene. The research interval was divided into five lithofacies based on lithological characteristics and sedimentary structures with Smd, Slc, Swy, Sfl and Ssf codes which were then grouped into three facies associations; mud flat, mixed flat, and sand flat. Based on the results of facies, biostratigraphy & bathymetry, electrofacies, and sequence stratigraphy analysis that have been integrated, the reservoir interval is interpreted as an association of tidal flat deposits in the tide dominated estuary environment with the age of Late Eocene. Facies associations in the study interval which are mud flat, mixed flat, and flat sand shows Northwest – Southeast trending of sedimentation. Static reservoir modelling consist of structural, facies, and petrophysical modelling were performed in order to determine reservoir geometries, property distributions, and hydrocarbon reserves estimation. Based on estimation, original gas in place (OGIP) at Reservoir 1 LECS A is 55.62 BCF and Reservoir 2 LECS B is 28.39 BCF.